Magma Chamber Associated to Deep Faults in Copahue Active Volcanic Complex, South America, Suggested by Magnetotelluric Study - E. Borzotta; A. T. Caselli; M. J. Mamani (Геофизический журнал, 2018)
Magnetotelluric studies were carried out in 1993 and 2008 inside the caldera of Copahue Volcanic Complex, located in South America, at the border between Chile and Argentina (37°45ʹ S; 71°10.2ʹ W). The main effusive centre of this complex is the Copahue Active Volcano, which constitutes an important geothermal zone. The study of the crust and the investigation of possible magma chambers were the objectives of this survey. Six magnetotelluric soundings were interpreted taking in mind the geologic and tectonic background. Two 2D bimodal modelling along two profiles approximately perpendicular to geological strike were performed. In addition, two magnetovariational studies were made, using two magnetic variometers. Induction (Wiese) vectors were thus estimated for three MT sites. Among the results, the lithosphere in the region is suggested to be 60—66 km thickness, with upper and lower crusts of 8 km and 10 km thickness respectively. A magma chamber is suggested at lower crust with top at 3—8 km depth, with 1 Ωm of resistivity, thus indicating partial-melting or melted-rocks. Data suggest this chamber could be genetically associated with a deep fault system into the caldera. Heat flows of 130—278 mW/m2 were estimated at surface, above magma chambers, using empirical formulas linking depths of thermal conductive layers, in the crust and upper mantle, with heat flows values measured at surface. The estimated heat flows, thus obtained, are rather consistent with heat flows measured in wells drilled into the caldera.